Perkembangan Kajian Hadis dalam Ranah Digital - Karima Nurul Huda; Akhmad Hasan Saleh; Kholila Mukaromah; Ibnu Hajar Ansori (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the development of hadith studies in the digital realm. This study uses a qualitative approach by applying descriptive analytical methods. The results of the research and discussion show that as time has progressed into the digital era, hadiths have begun to be packaged in it to display hadith studies more easily. This study concludes that with the development of hadith studies in this digital era, many hadith books have been digitized, namely a form of transfer of hadith books packaged in software which brings benefits and challenges to hadith scholars in particular and the whole community in general.